Spatially Resolving the Enhancement Effect in Surface-Enhanced Coherent Anti-Stokes Raman Scattering by Plasmonic Doppler Gratings - Ouyang, Lei (ACS Nano, 2020)
[Image: see text] Well-designed plasmonic nanostructures can mediate far and near optical fields and thereby enhance light–matter interactions. To obtain the best overall enhancement, structural parameters need to be carefully tuned to obtain the largest enhancement at the input and output frequencies. This is, however, challenging for nonlinear light–matter interactions involving multiple frequencies because obtaining the full picture of structure-dependent enhancement at individual frequencies is not easy. In this work, we introduce the platform of plasmonic Doppler grating (PDG) to experimentally investigate the enhancement effect of plasmonic gratings in the input and output beams of nonlinear surface-enhanced coherent anti-Stokes Raman scattering (SECARS). PDGs are designable azimuthally chirped gratings that provide broadband and spatially dispersed plasmonic enhancement. Therefore, they offer the opportunity to observe and compare the overall enhancement from different combinations of enhancement in individual input and output beams. We first confirm PDG’s capability of spatially separating the input and output enhancement in linear surface-enhanced fluorescence and Raman scattering. We then investigate spatially resolved enhancement in nonlinear SECARS, where coherent interaction of the pump, Stokes, and anti-Stokes beams is enhanced by the plasmonic gratings. By mapping the SECARS signal and analyzing the azimuthal angle-dependent intensity, we characterize the enhancement at individual frequencies. Together with theoretical analysis, we show that while simultaneous enhancement in the input and output beams is important for SECARS, the enhancement in the pump and anti-Stokes beams plays a more critical role in the overall enhancement than that in the Stokes beam. This work provides an insight into the enhancement mechanism of plasmon-enhanced spectroscopy, which is important for the design and optimization of plasmonic gratings. The PDG platform may also be applied to study enhancement mechanisms in other nonlinear light–matter interactions or the impact of plasmonic gratings on the fluorescence lifetime.